Mieux comprendre le transfert de connaissances en SST : propositions pour une typologie des guides de prévention - Isabelle Faurie; Frédéric Planché; Serge Deltor; Camille Ricaud; Anaïs Grau; Céline Guy (Perspectives Interdisciplinaires sur le Travail et la Santé)
The present study contributes to thinking on prevention guides, which are the main tools for knowledge translation in occupational health and safety. Based on an analysis of guides edited by ARACT Languedoc-Roussillon, the article presents a typology for prevention guides in OHS. Four categories of guides were identified: action, mediation, awareness, and information. The analysis shows that each type of guide fulfils a specific function in dynamic prevention. The interest that this categorization holds for the definition of better adapted prevention tools is discussed.